Bildungen auf -trächtig im Deutschen und ihre Entsprechungen im Polnischen - Koniuszaniec, Gabriela (Studia Germanica Posnaniensia, 2018)
In this article the author analysed -trächtig constructions in German along with their translational equivalents in Polish taking in to consideration the word-formation and semantic aspect. The foundation of the unilateral confrontation are examples taken from the press and literature stored in the so called Mannheim Corpus. Circa 70 word forms were analysed together with their occurrence contexts. When analysing the compounds mentioned in the title the author used the method of paraphrases either predicative or in the form of subordinate clauses or extended attributives. The method applied makes the choice of a proper equivalent easier in Polish. When in German univerbalization (Univerbierung) as it is called is the feature of the language in the analysed case, then in Polish shows tendencies to creating analytical constructions.